The Abolition of the Ottoman Caliphate, 1924 Debates and Implications - Giunchi, Elisa; Melis, Nicola (London Routledge, 2025)
This book explores the decision by the Grand National Assembly of Turkey in 1924 to abolish the caliphate. The Ottoman sultans had long borne the title of caliphs of Islam, with all the prestigious authority throughout the Muslim world that went with it, and in the aftermath of the First World War the caliphate still retained great symbolic relevance.The book considers the questions that arose with its abolition, including whether or not the caliphate should be revived, reformed or replaced by other forms of political affiliation and organization. It also assesses more general issues concerning identity and legitimate authority, and how to reconcile time-honoured religious institutions and concepts with modernity, the nation-state and affiliations of an ethnic and religious nature. The book additionally addresses the debates within the pan-Islamic congresses concerning the fate of the caliphate, and the implications of its abolition for Kurdish-Turkish relations and for the British and French Empires with their large Muslim populations.
E-Book / Zugriff nur im Lesesaal